Parent and youth dopamine D4 receptor genotypes moderate multilevel contextual effects on rural African American youth's risk behavior. (20th July 2015) - Cho, Junhan; Kogan, Steven M.
Abstract: The present investigation extends research on Gene × Environment interactions and youth risk behavior by linking multilevel contextual factors, such as community disadvantage and protective parenting practices, to both parental and youth dopamine D4 receptor ( DRD4 ) genotypes. We expected community disadvantage to influence youth risk behavior via a series of indirect effects involving protective parenting and youth's planful future orientation when both parents' and youth's DRD4 status was considered. Genetic moderation processes also were tested to determine whether they conformed to a diathesis–stress or a differential susceptibility model. Hypotheses were investigated with data from 361 rural African American youth and their parents assessed 3 times when youth were ages 16 to 19. Community disadvantage interacted with parental DRD4 status to predict low levels of protective parenting. Protective parenting, in turn, interacted with youth DRD4 status to forecast increases in youth's planful future orientations, a proximal influence on changes in risk behavior. The Parental DRD4 × Community Disadvantage interaction, but not youth DRD4 × Protective Parenting, conformed to a differential susceptibility model. Indirect effect analyses revealed a significant indirect path linking community disadvantage to youth risk behavior through a series of multilevel Gene × Environment interaction processes.